Multipronged attenuation of macrophage-colony stimulating factor signaling by Epstein–Barr virus BARF1 - Shim, Ann Hye-Ryong (National Academy of Sciences, 2012)
The ubiquitous EBV causes infectious mononucleosis and is associated with several types of cancers. The EBV genome encodes an early gene product, BARF1, which contributes to pathogenesis, potentially through growth-altering and immune-modulating activities, but the mechanisms for such activities are poorly understood. We have determined the crystal structure of BARF1 in complex with human macrophage-colony stimulating factor (M-CSF), a hematopoietic cytokine with pleiotropic functions in development and immune response. BARF1 and M-CSF form a high-affinity, stable, ring-like complex in both solution and the crystal, with a BARF1 hexameric ring surrounded by three M-CSF dimers in triangular array. The binding of BARF1 to M-CSF dramatically reduces but does not completely abolish M-CSF binding and signaling through its cognate receptor FMS. A three-pronged down-regulation mechanism is proposed to explain the biological effect of BARF1 on M-CSF:FMS signaling. These prongs entail control of the circulating and effective local M-CSF concentration, perturbation of the receptor-binding surface of M-CSF, and imposition of an unfavorable global orientation of the M-CSF dimer. Each prong may reduce M-CSF:FMS signaling to a limited extent but in combination may alter M-CSF:FMS signaling dramatically. The downregulating mechanism of BARF1 underlines a viral modulation strategy, and provides a basis for understanding EBV pathogenesis.